Moral regulating role of environmental cleanliness: Evidences from both practices and field experiments - Lu Li; Huangfu, Gang; Ma, Ran (Environment and Social Psychology, 2025)
Moral judgment and behavior have long been considered as the result of reasoning and conscious thought while contextual influence being downplayed. Cleanliness is a fundamental feature of the environment. Previous research relevant to cleanliness focused on body cleansing behavior’s effect on one’s moral consciousness. According to a view of anthropology, cleanliness, as a key environment feature, symbolizes social order. Thus, we contend that the state of environmental cleanliness may metaphorically link to the concept of public moral norm. Three studies were conducted in a manufacturing group company. Study 1, using ten-year monthly records of disciplinary violation rates during the implementation of 5S practices from four different companies of the same manufacturing group, showed that improving workplace cleaning, neatness, and cleanliness could reduce employees’ disciplinary violations. Study 2, by an experiment conducted at a real workplace, found that employees judged immoral workplace behaviors more morally wrong in the clean environment than in the dirty one; Meanwhile, conscientiousness trait weakens the effect of environmental cleanliness, whereas neuroticism trait strengthens this influence. Study 3, through an experiment priming awareness of workplace environmental cleanliness state, showed that employees showed harsher moral judgment on immoral workplace behaviors even when primed with the concept of clean environment than both the primed with the concept of dirty environment group and the control group. The results revealed the metaphorical association between the physical state of environmental cleanliness and the concept of abstract public moral norm, and provided a unique insight to the social significance of environmental cleanliness.